The development of a novel functional food: bioactive lipids in yogurts enriched with Aurantiochytrium sp. biomass. Issue 11 (16th October 2020) - Paulo, M. C.; Marques, J.; Cardoso, C.; Coutinho, J.; Gomes, R.; Gomes-Bispo, A.; Afonso, C.; Bandarra, N. M.
Abstract : The microalga Aurantiochytrium sp. is particularly rich in DHA and could be used as a nutraceutical in the preparation of innovative functional yogurts, whose lipid composition and bioaccessibility must be assessed. Abstract : Western diets are poor in healthy n3 polyunsaturated fatty acids, such as docosahexaenoic acid. Since microalga Aurantiochytrium sp. is rich in docosahexaenoic acid, a functional food based on lean yogurt and this microalga was tested. This study entailed characterizing the lipid fraction and determining the fatty acid bioaccessibility. The tested yogurts (control and 2% w/w, Aurantiochytrium sp.) had differences. Docosahexaenoic acid was not detected in the control product, but it was the second most important fatty acid in Aurantiochytrium sp. and Aurantiochytrium yogurt, 29.7 ± 0.4% and 18.7 ± 2.0%, respectively. Based on the fatty acid profile only, an amount of 158.7 g of Aurantiochytrium yogurt in wet weight terms would be required to ensure an appropriate intake of healthy fatty acids. Generally, the fatty acid bioaccessibility was not high, remaining below 60–70% in almost all cases. Considering the docosahexaenoic acid bioaccessibility (44 ± 3%), an amount of 360.7 g of Aurantiochytrium yogurt would be advisable. A reasonable dietary prescription would be a daily consumption of 125 ml of Aurantiochytrium yogurt.